Rapid review pathology - Goljan, Edward F. (Philadelphia, PA : Elsevier/Saunders, 2014)
This book is by Edward F. Goljan, MD, makes it easy for you to master all of the pathology material covered on the USMLE Steps 1 and 2. It combines an updated outline-format review of key concepts and hundreds of full-color images and margin notes, PLUS more than 400 USMLE-style online questions! Get all the practice you need to succeed on the USMLEs! New to this edition: Visualize key pathologic concepts and conditions with over 1,000 full-color images, completely reviewed and updated for this new edition.
Diagnostic testing -- Cell injury -- Inflammation and repair -- Immunopathology -- Water, electrolyte, acid-base, and hemodynamic disorders -- Genetic and developmental disorders -- Environmental pathology -- Nutritional disorders -- Neoplasia -- Vascular disorders -- Heart disorders -- Red blood cell disorders -- White blood cell disorders -- Lymphoid tissue disorders -- Hemostasis disorders -- Immunohematology disorders -- Upper and lower respiratory disorders -- Gastrointestinal disorders -- Hepatobiliary and pancreatic disorders -- Kidney disorders -- Lower urinary tract and male reproductive disorders -- Female reproductive disorders and breast disorders -- Endocrine disorders -- Musculoskeletal and soft tissue disorders -- Skin disorders -- Nervous system and special sensory disorders.
Includes bibliographical references and index.
Keywords: Pathology -- Outlines, syllabi, etc; Pathology -- Examinations, questions, etc; Pathology